Pelatihan Pembuatan Media Math Game Berbasis Android - Yuliana Trisanti; Hairus Saleh (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Most students consider mathematics as a difficult subject to understand, unpleasant and tends to be boring. Many students consider mathematics as a boring subject because all discussions of mathematics involve numbers and examples. This concept applies to all levels of education, both elementary, secondary and higher education. The purpose of this training is to explain methods that can increase students' interest in learning mathematics. The solution provided in this training is to help mathematics teachers in implementing mathematics learning using android games. The methods used in this community service are observation, planning, implementation and evaluation. Based on the results of this community service, it is concluded that the application of learning aids using a mathematics learning platform on an android game will increase students' interest in learning mathematics. This is evidenced by the increasing percentage of students who achieved the KKM above after the training. Before the training, the pre-test results showed that the proportion of students who scored above the KKM was only 20%. After guidance, the post-test results showed that the percentage of students who passed the KKM reached 85%. The benefit of this training is that it can increase students' interest in learning mathematics so that students do not view mathematics as a difficult and boring subject